Outing Heteronormativity in Interpersonal and Family Communication: Feminist Applications of Queer Theory "Beyond the Sexy Streets". (19th March 2013) - Chevrette, Roberta
<x xml:space="preserve">Abstract</x> Within interpersonal and family communication, researchers have tended to construct and describe LGBTQ relationships in regard to a heterosexual norm. A review of recent research reveals the conceptual limitations of this framework, "outing" heteronormativity's influence on our understandings of nonheterosexual relationships. I outline the challenges of "queering" interpersonal and family communication research and argue that feminist theory can contribute to this process by (a) revealing the heteronormative assumptions perpetuated by dyadic models of communication, (b) challenging the public/private bifurcation, (c) complicating notions of identity, and (d) emphasizing intersectionality. The article concludes by discussing the implications a feminist queer perspective holds for interpersonal and family communication pedagogies and research.